llllllllllll ajude-me
![Llllllllllll Ajudeme class=](https://pt-static.z-dn.net/files/d53/885503f877fef378c5259f6d6260414b.jpg)
[tex]\Large\boxed{\boxed{\boxed{{Ola\´\ }}}}}[/tex]
▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃
a) PAR ✅
[tex]f(x) = \frac{ {5x}^{2} }{2} \\ \\ f( - x) = \frac{ {5.( - x)}^{2} }{2} \\ \\ f( - x) = \frac{ {5x}^{2} }{2} \\ \\ f( - x) = f(x)[/tex]
➖➖➖➖➖➖➖➖➖➖➖➖
b) PAR ✅
[tex]f(x) = {x}^{2} - 1 \\ f( - x) = {( - x)}^{2} - 1 \\ f( - x) = {x}^{2} - 1 \\ f( - x) = f(x)[/tex]
➖➖➖➖➖➖➖➖➖➖➖➖
c) NEM PAR NEM ÍMPAR ❌
[tex]f(x) = {x}^{2} - 5x + 6 \\ f( - x) = {( - x)}^{2} - 5.( - x) + 6 \\ f( -x) = {x}^{2} + 5x + 6[/tex]
➖➖➖➖➖➖➖➖➖➖➖➖
d) ÍMPAR ✅
[tex]f(x) = \frac{ {x}^{2} - 3}{ {x}^{3} } \\ \\ f( - x) = \frac{ {( - x)}^{2} - 3}{ {( - x)}^{3} } \\ \\ f( - x) = \frac{ {x}^{2} - 3}{ { - x}^{3} } \\ \\ f( - x) = \frac{3 - {x}^{2}}{ {x}^{3} } \\ \\ f( - x) = \frac{ - ({x}^{2} - 3)}{ {x}^{3} } \\ \\ f( - x) = - \frac{{x}^{2} - 3}{ {x}^{3} } \\ \\ f( - x) = - f(x)[/tex]